1970
DOI: 10.4314/ahs.v19i4.42
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and utilization of institutional voluntary HIV testing and counseling services among students aged 18-24 in Kenya’s public Universities

Abstract: Background: Kenya is home to an estimated 1.7 million people living with HIV/AIDS. According to the Kenya AIDS Indicator survey KAIS 2012, HIV prevalence in the age group 15-24 stood at 2.2%. Globally, young people aged 15-24 are a highly vulnerable population with respect to HIV/AIDS infection and transmission. HIV testing and counseling services play a critical role as an entry point to care and treatment. However, uptake of HIV testing and counseling services among the youth in Kenya has been reportedly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 8 publications
5
14
1
Order By: Relevance
“…This finding showed that discussing HIV testing with family members is significantly associated with testing of family members. This is similar with studies conducted in Mekelle hospital, Ethiopia, 21 Felege Hiwot Referral Hospital, Ethiopia, 10 and Ndola, Zambia. 15 The possible reason for this association is that discussion about testing is a pre-condition for tracing family members for testing and results in a favourable situation for the index client to bring their families for testing.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding showed that discussing HIV testing with family members is significantly associated with testing of family members. This is similar with studies conducted in Mekelle hospital, Ethiopia, 21 Felege Hiwot Referral Hospital, Ethiopia, 10 and Ndola, Zambia. 15 The possible reason for this association is that discussion about testing is a pre-condition for tracing family members for testing and results in a favourable situation for the index client to bring their families for testing.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with studies conducted in Assosa, Ethiopia, 18 Uganda, 19 and Zambia. 20 , 21 The reason for this could be that disclosure of HIV positive status plays an important role for both to the infected individual and to the family at large. It adequately addresses emotional, social, and practical consequences of the disease among the families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A larger proportion of the students were informed about VCT and also, knew where VCT services were provided [26]. This was consistent with previous studies [27,7,8,19,28,21] but contrary to others [29,30,8]. The higher VCT knowledge and uptake could be attributed to the efforts of the National HIV/AIDS control program (NACP) with support from local and international partners which have held a sustained sensitization program on HIV/AIDS in Ghana over the years through the mass media and the hospitals.…”
Section: Discussionsupporting
confidence: 86%